STRATEGY IN DEVELOPING CLOVE FARMING AT NORTH TINANGKUNG DISTRICT OF BANGGAI ISLAND - Mohamad Wahyudi; Saiful Darman; Made Antara (Tadulako University, 2016)
This research is aimed at determining strategy for developing Clove Farming in Banggai Kepulauan district. The research site is chosen purposively based on the consideration that the site has become one of the districts favored for clove farming development in Banggai Kepulauan district. The sample was taken by employing simple random sampling methode 15% from the village population.Total number of respondents was 24. The data analysis employed in this research was SWOT. Results of SWOT analysis indicated that clove farming belonged to III quadran (supporting turn around strategy) with WO strategy (weakness-opportunities). Programme or activity proposed, includes: (1) Application of business oriented management with the use of technology development, (2) Linkages with partners/cooperation with financial institution for capital assisstance, and (3) Cooperation with academics/government institution for human resource development